Review the Utilization of Resistant Starch in Aking Rice Flour as Anti-Diabetic Food Ingredients - Aini, Nur; Dewi, Sinta; Asyifa, Soniya Nur; Sofyan, Aan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Aking rice is dried leftover rice that has been cooked and has not been consumed, so it will become stale rice then dried and considered by some people as household food waste. Thus far, aking rice has been used more for animal feed rather than being processed into human’s food. At the same time, the prevalence of type 2 Diabetes Mellitus (DM) sufferers in developing countries including Indonesia is increasing. This review article will describe the opportunities for using aking rice to be processed into alternative food for people with type 2 diabetes. The writing of this article uses the Secondary Data Analysis (SDA) approach and literatur review in line with PRISMA. From the results of the review article, it is known that aking rice not only have a low glycemic index value, but also contains resistant starch (starch resistant) which can be beneficial for people with type 2 diabetes. The utilization of aking rice can through processed into aking rice flour. This flour can applied to the processing of various food products for people with diabetes type 2.